Perl Programming for Bioinformatics - Harshawardhan P. Bal (Tata McGraw-Hill, 2003)
This book introduces Bioinformatics and its tools and techniques to a new hybrid professional the biologist and the would-be informatician and encourages to use this vast and powerful resource to address biological problems.